Comparison of fibula plating versus fibula nailing: A systematic review with meta-analysis of all current comparative literature - Troy B Puga; McKenna W Box; Charles R Marchese; Alan Lam; Sam Stegelmann; John T Riehl (Journal of Orthopaedic Surgery)
Ankle fracture surgeries are common orthopaedic procedures. Fibular fixation is often an important component in restoring ankle stability. Fibular intramedullary nailing (fIMN) has gained recent interest as an alternative technique to fibular plating. This systematic review and meta-analysis was performed to compare the outcomes of fibular nailing versus fibular plating for all current available literature. A PRISMA-compliant systematic review was conducted across MEDLINE/Pubmed, Cochrane, and Embase databases for cohort and clinical trial studies comparing outcomes of fibular nailing and fibular plating of ankle fractures. Demographics and results of the studies were extracted from the articles. Outcomes of interest extracted included operative time, functional outcomes scores, hardware/loss of reduction, malunion/nonunion, re-operations, and wound complications. Meta-analysis of included studies used odds ratios and standardized mean difference when appropriate. Nine studies were included in this systematic review. Eight studies were then used for meta-analysis comparison. fIMN showed equivalent operating times to fibular plating. fIMN had equivalent outcomes when compared with fibular plating for hardware failure/loss of reduction, Olerud and Molander Ankle Score, malunion/nonunion, and re-operations. Fibular nailing showed a decrease in wound complications (OR: 0.35 [0.18, 0.66] ( p = .001)) when compared with fibular plating. fIMN showed equivalent outcomes and decreased wound complications compared to fibular plating. fIMN is a safe and effective alternative treatment method that can be used by surgeons to treat distal fibula fractures. Level of Evidence 3.